A Child with Severe Paraesthesia due to Pyrethroid Exposure: Successful Treatment with Topical Vitamin E - Aykut Çağlar; Anıl Er; Emel Ulusoy; Fatma Akgül; Dorukhan Besin; Hurşit Apa (Galenos Yayinevi, 2020)
Pyrethroids are one of the most common insecticides and have been known as safe household insecticides. They are highly toxic for insects whereas they are low in toxicity for mammals. Poisoning syndromes occur via oral, dermal or respiratory exposure. Dermal paraesthesia is the most common symptom in cases of unintentional dermal exposure. Although mild dermal paraesthesia cases are commonly seen after occupational exposure, severe cases are rare in the literature. Thus, emergency physicians may have difficulties in terms of managing these patients. Here, we report a child with diffuse paraesthesia and agitation after 24 hours from insecticide exposure. The patient was well treated with topical vitamin E in our pediatric emergency department.